2022
DOI: 10.1371/journal.pone.0267038
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir plus Dexamethasone in COVID-19: A cohort study of severe patients requiring high flow oxygen therapy or non-invasive ventilation

Abstract: Introduction Remdesivir and Dexamethasone represent the cornerstone of therapy for critically ill patients with acute hypoxemic respiratory failure caused by Coronavirus Disease 2019 (COVID-19). However, clinical efficacy and safety of concomitant administration of Remdesivir and Dexamethasone (Rem-Dexa) in severe COVID-19 patients on high flow oxygen therapy (HFOT) or non-invasive ventilation (NIV) remains unknown. Materials and methods Prospective cohort study that was performed in two medical Intensive Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Non-invasive sequential ventilation treatments are simple to perform and cause less trauma to the body. Some studies have indicated that this type of therapy has little effect on the gastrointestinal tract and can effectively correct body hypoxia [17,18]. However, research has also proven that mechanical ventilation alone can be insufficient in terms of secretion drainage compensation, thus creating a limitation of its single application [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive sequential ventilation treatments are simple to perform and cause less trauma to the body. Some studies have indicated that this type of therapy has little effect on the gastrointestinal tract and can effectively correct body hypoxia [17,18]. However, research has also proven that mechanical ventilation alone can be insufficient in terms of secretion drainage compensation, thus creating a limitation of its single application [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian tersebut, pasien diberikan antiinflamasi (deksametason dan aspirin), 21 sehingga faktor ini mungkin berperan dalam perbaikan kadar enzim hati. [22][23][24] Pemberian remdesivir tidak menjadi kontraindikasi absolut apabila nilai SGOT dan SGPT tidak melebihi 10 kali batas normal. 25 Kadar NLR, PLR, dan feritin sebelum terapi remdesivir juga terpantau lebih tinggi pada laki-laki dibandingkan perempuan.…”
Section: Bahasanunclassified
“…However, the study could not find conclusive results regarding adverse events or hospital-acquired bacterial infection rates due to its use. 14,24 In the index study, 97.1% of patients received systemic corticosteroids, mostly injectable dexamethasone. No comparative assessment could not be done between steroid and non-steroid recipients.…”
Section: Specific Treatment and Add-on Therapymentioning
confidence: 99%